2013
DOI: 10.1001/jamasurg.2013.1560
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Tranexamic Acid on Clopidogrel Before Coronary Artery Bypass Grafting

Abstract: Preoperative clopidogrel exposure increased bleeding and transfusion requirements in patients receiving on-pump CABG. Tranexamic acid reduced this risk and provided extra protection selectively in the patients with persistent clopidogrel exposure within 7 days before surgery. TRIAL REGISTRATIONL clinicaltrials.gov Identifier: NCT01060163.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 23 publications
1
39
0
2
Order By: Relevance
“…The World Health Organization lists TXA as an essential medication . It is an antifibrinolytic drug and a synthetic derivative of the amino acid lysine that reduces plasmin concentration by blocking the lysine‐binding sites of plasminogen, which in turn inhibits the binding of plasminogen to fibrin and then conversion of plasminogen to plasmin . Plasmin via the complement system may interfere with platelet function and reduce platelet adhesion and aggregation…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization lists TXA as an essential medication . It is an antifibrinolytic drug and a synthetic derivative of the amino acid lysine that reduces plasmin concentration by blocking the lysine‐binding sites of plasminogen, which in turn inhibits the binding of plasminogen to fibrin and then conversion of plasminogen to plasmin . Plasmin via the complement system may interfere with platelet function and reduce platelet adhesion and aggregation…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the clopidogrel analyses it is understood that many of the cases were also on aspirin. Furthermore, many of the included studies were pre‐2000 when use of tranexamic acid, which has been shown to reduce blood loss in both aspirin‐ and clopidogrel‐treated patients (McIlroy et al , ; Shi et al , ), was less prevalent. Hence, most recent cardiac guidelines recommend continuing aspirin pre‐CABG unless there is a very high bleeding risk, a very low thrombosis risk or the patient would decline transfusion (Ferraris et al , ; Sousa‐Uva et al , ).…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…Zgłaszane odsetki krwawień podczas CABG u pacjentów z NSTE-ACS wahają się od 64% do 80% zależnie od stosowanej definicji i czasu, który upłynął między zaprzestaniem DAPT a operacją [284,285]. Incydenty krwotoczne, jak również przetoczenia krwi podczas CABG są związane ze zwiększoną chorobowością i śmiertelnością [286,287].…”
Section: Krwawienie Związane Z Pomostowaniem Aortalno-wieńcowymunclassified